Effect of LiTFSI Electrolyte Salt Composition on Characteristics of PVDF-PEO-LiTFSI-Based Solid Polymer Electrolyte (SPE) for Lithium-Ion Battery - Hasim Muzadi; Nayla Zahra Kamalia; Titik Lestariningsih; Yayuk Astuti (Molekul, 2023)
A lithium-ion battery with PVDF-PEO synthetic polymer sheet added by LiTFSI electrolyte salt has been made by assembling method. This study aims to determine the effect of LiTFSI salt concentration on the performance of lithium-ion batteries. The composition of LiTFSI electrolyte salts was varied into 5%; 10%; 15%; and 20%. Several characterizations were carried out to determine battery performance, including Electrochemical Impedance Spectrometry (ElS), Cyclic Voltammetry (CV), Charge/Discharge (CD), and Lithium Transference Number (LTN). The results showed that the synthesized separator sheet with a LiTFSI salt composition of 20% producing voltage, ionic conductivity, and lithium-ion transfer number of 0.72 V; 3.94 x 10-8 SCm-1; and 0.895, respectively is potential for lithium-ion batteries application. These results indicate the use of LiTFSI electrolyte salts with a concentration of 20% shows the best performance for PVDF-PEO-LiTFSI-based lithium-ion batteries.